Chemical Compound Of Ethanol Extract From Seluang Malik (Leea Amabilis Veitch Ex Mast) Potential As An Anti-Diabetes - Rosamah, Enih; Kusuma, Irawan Wijaya; Arung, Enos Tangke; Wicaksono, Dian Anggoro; Dungani, Rudi (Ann Publisher, 2025)
Background. The Bahau ethnic group in East Kalimantan has employed the roots and leaves of the L. amabilis plant as an anti-diabetic remedy. Thus, scientific verification of this herb is required. Aims. The goal of this study is to examine the bioactive compounds, the anti-diabetic potential, and the chemical composition of L. amabilis ethanolic extracts. Methods. Phytochemical analyses, -amylase enzyme activity assays, DPPH free radical scavenging activity tests, and GC/MS chemical compound analyses were used as experimental methodologies. Result. The findings demonstrated the presence of flavonoids, tannins, steroids, carbohydrates, and carotenoids in the leaf extracts. Alkaloid, tannin, triterpene, and carbohydrates were present in the root extracts. Alkaloid, tannin, triterpene, and carbohydrates were present in the root extracts. The antioxidant and anti-diabetic activity of the L. amabilis leaves extract is higher than that of the root. A significant chemical in the leaves and roots of L. amabilis has been identified as endo-Borneol. Conclusion. A substantial chemical in the leaves and roots of L. amabilis has been identified as endo-Borneol. Endo-Borneol from leaves of L. amabilis showed a chromatographic peak at R. Time of 7.327, area of 2483598, area% of 43.64%, height of 956167, and A/H of 2.60. Nevertheless, the Endo-Borneol chromatographic peak from the root of L. amabilis was found at R. Time of 7.605, area of 889232, area% of 100%, height of 49189, and A/H of 18.08. Implementation. The findings of the study highlight the need for further processing of natural antioxidant and anti-diabetic compounds made from L. amabilis leaves.